The role of Sciences of History, Philosophy and Epistemology of Science in changes in conceptions on the nature of science in future teachers (Research, Society and Development, 2020)
The debate about the inclusion of History and Philosophy in science education has been developed for a long time. However, a simplistic view of the nature of scientific knowledge among students and teachers still prevails. This research studied the conceptions of undergraduate students in an Exact Sciences course at a public university in Western Paraná. The research was carried out over 3 years and was based about History, Philosophy and Science Teaching of the 3rd semester and the discipline of Epistemology of the 5th semester. Open questionnaires were carried out at the beginning and at the end of the disciplines, which were analyzed using the Discursive Textual Analysis approach. The results show that, although timid, there is a significant change in the students' conceptions over the years, especially regarding the methodological issues of the production of scientific knowledge.